Surgical Management of a Functional Paraganglioma of the Infratemporal Fossa - Tritter, Andrew G.; Selber, Jesse; Kupferman, Michael E. (Journal of Neurological Surgery Reports, 2015)
Background Paragangliomas are rare neural crest tumors that can manifest in the head and neck as either functional or more commonly as nonfunctional lesions. Paragangliomas of the infratemporal fossa are exceedingly rare, with no more than a handful of documented cases. Like other tumors of this space, surgical management is challenging on account of complex anatomy and nearby critical structures.Methods A 44-year-old man presented with a right infratemporal fossa functional paraganglioma. Following preemptive embolization and autonomic pharmacotherapy, his tumor was successfully resected via a transfacial maxillary swing approach.Results This case highlights the surgical management of a functional paraganglioma of the infratemporal fossa while demonstrating the effectiveness of a transfacial maxillary swing approach for both exposure and resection.Conclusion Although this report summarizes much of the literature on paragangliomas, there is still much to uncover regarding the fundamental features and genetic etiology of these lesions.
Keywords: functional paraganglioma; infratemporal fossa; maxillary swing; glomus tumor